Effect of fish bone gelatin supplementation on protein contents and acceptability of rice-based traditional food - . Kasmiati; . Metusalach; Muh. Kasim (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
This research was aimed at determing the effect of fish bone gelatin supplementation on protein content and consumer acceptability of rice-based traditional foods. Three types of traditional foods, i.e. dange, surabeng andonde-onde were supplemented with fish bone gelatin at concentrations of 0, 5, 10, 15 and 20% (w/w) with three replicates for each treatment and for each type of foods. The protein contents were analyzed using micro-kjeldahlmethod whereas the consumer acceptability was determined organoleptically by employing 15 panelists. Data on the protein contents were subjected to ne-way Annova, while those of consumer acceptability were analyzed descriptively using percentage of frequency of occurrence. Results indicated that addition of fish bone gelatin significantly increased the protein contents of the foods and that the protein content of each type of foods was differ between the gelatin concentration treatments. The protein contents of foods were increased by 1.68-4.77 folds, and may be predicted using a simple regression formula: Y=0.578x + 6.037, R2=0.978 for dange; Y=0.660x + 4.068, R2=0.992 for surabeng; and Y=0.554x +5.39, R2=0.967 for onde-onde. The level of consumer acceptability showed that the addition of 10% of fish bone gelatin into each of the three traditional foods produced food products with good acceptability levels.